Demographic dynamics in Bangladesh : looking at the larger picture - Centre for Policy Dialogue (Bangladesh); United Nations Population Fund.; CPD-UNFPA Programme on Population and Sustainable Development (Dhaka : Pathak Shamabesh, 2003)
Contributed articles.
"Prepared under the CPD-UNFPA Programme on Population and Sustainable Development".
Includes statistical tables.
Includes bibliographical references and index.
Keywords: Sustainable development -- Bangladesh; Bangladesh -- Population